Agriculture: Innovations in Vertical Cultivation Systems for Community Development - Muhammad Syamil, Mohd Yusof; Azimah, Ismail; Norliana, Yusoff; Rafeah, Wahi (EDP Sciences, 2023)
This paper explores potential barriers to the adoption of soil-less, small-scale hydroponic systems operated through digital technology within gardening communities and related projects. It investigates whether these communities view a technology-driven approach to food cultivation as limiting. The backdrop of the COVID-19 pandemic highlights interconnected challenges spanning food security, climate change, and economic turmoil. Disruptions in global supply chains and economic activities resulting from the pandemic have precipitated an economic crisis, income disparities, and increased food insecurity. Agricultural disruptions have exacerbated food security issues, while climate change-induced extreme weather events further jeopardize food systems. This economic crisis impedes effective climate change mitigation and adaptation. A holistic approach is crucial, integrating sustainable agriculture, resilient food systems, and climate change strategies. Collaboration among governments, researchers, and communities is vital for enduring food security and sustainable economies. The Hydroponic Verticulture System (HVS), a modern urban agricultural technology, offers a practical solution that fosters ensures food quality, and supports community engagement. A full tank of water or mixed organic material of 13.5 Liter with 5rm speed provided sufficient watering for effective nourishment and hydration throughout the vertical system. Furthermore, HVS contributes to climate change mitigation by reducing CO2 and increasing O2 levels through smart urban farming practices, aligning with environmental sustainability goals.